2014
DOI: 10.1504/ajmsa.2014.070649
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable value analysis tool for value creation

Abstract: She has a Bachelor's degree in Mechanical Engineering and a Master's degree in Industrial Engineering. Her current research seeks to understand how manufacturing companies create sustainable value. She is interested in sustainable business models, sustainable product-service systems development, and industrial symbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 20 publications
(30 reference statements)
0
40
0
Order By: Relevance
“…In order to better understand the concept of value uncaptured, this paper develops the four forms of value uncaptured from previous work (Yang et al, 2014) shown in Figure 2. · Value surplus (VS) is value which exists, but is not required.…”
Section: Theoretical Framework: Value Uncaptured Perspective For Sustmentioning
confidence: 99%
“…In order to better understand the concept of value uncaptured, this paper develops the four forms of value uncaptured from previous work (Yang et al, 2014) shown in Figure 2. · Value surplus (VS) is value which exists, but is not required.…”
Section: Theoretical Framework: Value Uncaptured Perspective For Sustmentioning
confidence: 99%
“…Given such a multidimensional and complex concept (Laasch, ), designing BMs in order to adequately encapsulate sustainable value becomes a major challenge (Biloslavo, Bagnoli, & Edgar, ; Hart & Milstein, ). Furthermore, extant modeling and design methods for BMs are limited and rarely geared towards sustainable value (Evans et al, ; Yang, Vladimirova, Rana, & Evans, ; Zott & Amit, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A number of firms have witnessed the potential of PSS to bring significant revenue and meanwhile reduce negative environmental impact (Baines et al 2007;Tukker 2004;Yang, Evans, et al 2017). Some researchers investigate how sustainability could be embedded into PSS development (Geum and Park 2011;Manzini and Vezzoli 2003;Yang 2015), and a number of methods and tools have been developed to assist companies develop sustainable PSS business models or increase sustainable value creation in PSS, such as (Matzen and McAloone 2006;Yang et al 2014).…”
Section: Product-service Systemsmentioning
confidence: 99%